Benefit of technetium‐99m galactosyl human serum albumin scintigraphy instead of indocyanine green test in patients scheduled for hepatectomy. Issue 10 (7th January 2014) - Ohkura, Yasuo; Mizuno, Shugo; Kishiwada, Masashi; Hamada, Takashi; Usui, Masanobu; Sakurai, Hiroyuki; Tabata, Masami; Yamada, Tomomi; Isaji, Shuji
<x xml:space="preserve">Abstract</x> Aim The aim of this study was to evaluate the benefit of technetium‐99m galactosyl human serum albumin (99mTc‐GSA) scintigraphy instead of the indocyanine green retention rate at 15 min (ICGR15) in the patients scheduled for hepatectomy, paying special attention to the factors causing the discrepancy between the ICGR15 and the hepatic uptake ratio of 99mTc‐GSA scintigraphy at 15 min (LHL15). Methods The medical records on the 197 patients who underwent hepatectomy between 2006 and 2010 were retrospectively reviewed. We defined ICG‐good as less than 15% at ICGR15 and ICG‐poor as 15% or more, and LHL‐good as 0.9 or more at LHL15 and LHL‐poor as less than 0.9. Results The patients were divided into the four groups ICG‐good/LHL‐good, ICG‐good/LHL‐poor, ICG‐poor/LHL‐good and ICG‐poor/LHL‐poor, showing the discrepancy between the two tests in 47 (23.8%) patients. In the ICG‐good group, the incidence of liver cirrhosis (LC) was significant higher in the ICG‐good/LHL‐poor group than in the ICG‐good/LHL‐good group at 54.5% versus 14.9% (P = 0.014). In the ICG‐poor group, the incidence of LC was significant lower in the ICG‐poor/LHL‐good group than in the ICG‐poor/LHL‐poor group at 44.4% versus 77.8% (P = 0.004). In multivariate analysis of the factors causing discrepancy, the factor contributing to LHL‐poor was hepatitis C infection and those contributing to LHL‐good were albumin and hyaluronic acid. Conclusion 99mTc‐GSA scintigraphy is very helpful to assess the hepatic functional reserve in the ICG‐good patients who have hepatitis C infection and in the ICG‐poor patients who have relatively good levels of albumin and hyaluronic acid.